2018
DOI: 10.1126/science.aap9310
|View full text |Cite
|
Sign up to set email alerts
|

An autoimmune disease variant of IgG1 modulates B cell activation and differentiation

Abstract: The maintenance of autoreactive B cells in a quiescent state is crucial for preventing autoimmunity. Here we identify a variant of human immunoglobulin G1 (IgG1) with a Gly 396 →Arg substitution (hIgG1-G396R), which positively correlates with systemic lupus erythematosus. In induced lupus models, murine homolog Gly 390 →Arg (G390R) knockin mice generate excessive numbers of plasma cells, leading to a burst of broad-spectrum autoantibodies. This enhanced production of antibodies is also observed in hapten-immun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
24
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(28 citation statements)
references
References 28 publications
1
24
0
Order By: Relevance
“…35 These autoantibodies may play an important role in the pathogenesis of SLE. 69 Identifying new autoantibodies will benefit our understanding of SLE diagnosis and therapy.…”
Section: Introductionmentioning
confidence: 99%
“…35 These autoantibodies may play an important role in the pathogenesis of SLE. 69 Identifying new autoantibodies will benefit our understanding of SLE diagnosis and therapy.…”
Section: Introductionmentioning
confidence: 99%
“…Pristane-induced lupus-like animal model was used to reflect the disease of SLE in this study, as the accelerated cells death and the presentation of apoptotic debris as autoantigen are considered as the mainly mechanisms of this model [36]. Bm12- induced cGVHD model was another lupus-like autoimmunine model [37] and was also utilized in the current study to identify the effect of SMS1 on SLE-like autoimmunity. In bm12-induced lupus-like model, cognate recognition of the MHC II in recipient B cells by donor CD4 + T cells results in extensive activation of host B cells and production of auto-Abs from recipient B-lymphocytes [38].…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, SNP associations have been reported in IGHG3 * 18 (S176Y SNP:rs201430154) to increase the risk of inhibiting components of protein replacement therapies in hemophilia (69). The importance of considering non-allotypic allelic variation is further highlighted by the discovery of a SNP in the cytoplasmic tail of IgG1 which is prevalent in cases of systemic lupus erythematosus (57). This variant has major implications for the humoral response upon infection or vaccination, and in autoimmune disorders, by enhancing IgG1 expression.…”
Section: Implications Of Constant Domain Diversity In Diseasementioning
confidence: 92%
“…Immunoglobulin allotypes and haplotypes have long been associated with susceptibility to infections and diseases including breast cancer (56), autoimmunity (57,58), malaria (39,59), herpes (16,60,61), and hepatitis C (62,63). More recently, studies have even linked constant domain diversity to longevity observed in certain populations (64).…”
Section: Implications Of Constant Domain Diversity In Diseasementioning
confidence: 99%